GE_GERICHTE C/23245/2017 vom 4. Oktober 2018 - GE Cour de justice (2018)
MAINLEVÉE PROVISOIRE ; ERREUR ESSENTIELLE ; LOCATAIRE DE REMPLACEMENT ; BAIL À LOYER | LP.82; CO.258.al1; CO.23; CL.22.al5; CO.24.al1.ch4